Myocardial Calcinosis a Case Report - Özeren, Naciye; Yıldırım, Ferhat; Çekin, Necmi; Erdönmez, Filiz (The Bulletin of Legal Medicine, 2014)
Myocardial calcification (myocardial calcinosis) is a rare condition in the literature. Meta-static or dystrophic calcification can be seen in two types. Chronic renal failure, hemodialysis, sec-ondary hyperparathyroidism, hypercalcemia, the blood calcium level as high phenomena that are associated with metastatic calcification. In dystrophic calcification, normal blood calcium levels, normal kidney functions, normal coronary artery are observed. Myocardial calcification as a result of congestive heart failure, fatal arrhythmias, heart valve dysfunction, myocardial infarction may occur. Case: 35 years old Syrian male. In the civil war in Syria bombing injured as a result, nearly two months in various hospitals and treated for renal failure developing died. Evaluated within the scope of forensic autopsy has been decided. At autopsy; scar tissue due to previous operations, in-ternal examination in both kidneys logy was found the abse formation. Microscopy: Lobular pneu-monia, atelectasis, edema in the lung. Retroperitoneal active chronic inflammation, inflammatory exudate, bleeding, abscesses and abscess wall was detected. The coronary arteries were normal. myocardial more pericardial and myocardial tissue including tissue calcification was found in the common. Renal failure caused by a lack of calcium in blood as myocardial calcinosis was evaluat-ed. These deposits often may actually on the whole body, generally, vessels, kidneys, lungs, interstitial tissues of gastric mucosa holds. Pericardium and in myocardial tissue is extremely rare, interesting case is presented here. Key Words: Hypercalcemia, Calcification, Myocardial.